2021
DOI: 10.1016/j.gendis.2019.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive biological function analysis of lncRNAs in hepatocellular carcinoma

Abstract: Thousands of long non-coding RNAs (lncRNAs) have been discovered in human genomes by gene chip, next-generation sequencing, and/or other methods in recent years, which represent a significant subset of the universal genes involved in a wide range of biological functions. An abnormal expression of lncRNAs is associated with the growth, invasion, and metastasis of various types of human cancers, including hepatocellular carcinoma (HCC), which is an aggressive, highly malignant, and invasive tumor, and a poor pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 120 publications
(123 reference statements)
0
7
0
Order By: Relevance
“…ADIPOQ, which was identified as an adipose gene in 1996 [64] , might be a candidate gene for renal disease and diabetes [65] . AL356479.1 has – as MALAT1 – been associated with breast cancer [66] and appears to have significant effect on breast cancer survival [67] . This could be due to the majority of the tissue donors in Emont et al’s study being female [18] and might indicate existing or future health problems for some of the study participants, or might indicate a so far unknown function of AL356479.1 in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…ADIPOQ, which was identified as an adipose gene in 1996 [64] , might be a candidate gene for renal disease and diabetes [65] . AL356479.1 has – as MALAT1 – been associated with breast cancer [66] and appears to have significant effect on breast cancer survival [67] . This could be due to the majority of the tissue donors in Emont et al’s study being female [18] and might indicate existing or future health problems for some of the study participants, or might indicate a so far unknown function of AL356479.1 in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous previous studies have demonstrated that lncRNAs play regulatory roles in various biological processes, including the cell cycle, cell differentiation, apoptosis, migration, invasion, and cancer progression (13)(14)(15)(16)(17). There is accumulating evidence that lncRNAs may also act as competing endogenous RNAs (ceRNAs) that are able to adsorb microRNAs (miRNAs/ miRs), and thus influence tumorigenesis (18,19). For example, lncRNA long intergenic non-protein coding RNA 2620 (BCRT1) was found to promote breast cancer progression by binding with miR-1303 (20).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor hypoxia is one of the adverse factors for cancer treatment, and it participates in HCC occurrence and significantly increases HCC invasiveness [ 7 ]. LncRNA can act on miRNA to further target and regulate mRNA, all of which form the lncRNA/miRNA/mRNA regulatory axis, and then participate in the occurrence, development and metastasis of hepatocellular carcinoma [ 16 , 17 ]. The construction of the ceRNA networks under hypoxia is helpful for us to comprehend the molecular mechanism of hypoxia-related genes in hepatocellular carcinoma and find new prognostic markers and treatment entry points for hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%